Value of Pretreatment 18F-fluorodeoxyglucose Positron Emission Tomography in Patients With Localized Pancreatic Cancer Treated With Neoadjuvant Therapy - Barnes, Chad A.; Aldakkak, Mohammed; Clarke, Callisia N.; Christians, Kathleen K.; Bucklan, Daniel; Holt, Michael; Tolat, Parag; Ritch, Paul S.; George, Ben; Hall, William A.; Erickson, Beth A.; Evans, Douglas B.; et al. (Frontiers in Oncology, 2020)
Background: 18F-fluorodeoxyglucose positron emission tomography/computed tomography (PET/CT) imaging is not routine in patients with localized pancreatic cancer (PC). We evaluated the prognostic value of PET/CT in patients who received neoadjuvant therapy. Methods: Patients with localized PC had pretreatment PET/CT with or without posttreatment (preop) PET/CT. Maximum standardized uptake values (SUV) were classified as high or low based on a cut point of 7.5 (diagnosis; SUVdx) and 3.5 (preoperative; SUVpreop), respectively. Preoperative carbohydrate antigen 19-9 (CA19-9) was classified as normal (≤35 U/mL) or elevated. Results: Pretreatment PET/CT imaging was performed on 201 consecutive patients; SUVdx was high in 98 (49%) and low in 103 (51%). Preop PET/CT was available in 104 (52%) of the 201 patients; SUVpreop was high in 60 (58%) and low in 44 (42%). Following neoadjuvant therapy, preop CA19-9 was normal in 90 (45%) patients and elevated in 111 (55%). Median overall survival (OS) of all patients was 27 months; 44 versus 13 months for patients that did (n=148, 74%) or did not (n=53, 26%) complete all neoadjuvant therapy and surgery (p<0.001). Median OS was 33 months for the 103 patients with a low SUVdx and 22 months for the 98 patients with a high SUVdx (p=0.03). Median OS for patients with low SUVdx/normal preop CA19-9, high SUVdx/normal preop CA19-9, low SUVdx/elevated preop CA19-9, and high SUVdx/elevated preop CA19-9 were 66, 34, 23, and 17 months, respectively (p<0.0001). Conclusion: Pretreatment PET/CT avidity and preoperative CA19-9 are clinically significant prognostic markers in patients with PC.